China and its Dollar exchange rate: A worldwide stabilizing influence? - Ronald McKinnon; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2011)
We argue that criticism concerning the Chinese dollar peg is misplaced as no predictable link exists between the exchange rate and the trade balance of an international creditor economy. The stable nominal yuan/dollar rate is argued to have stabilized Chinese, East Asian and global growth. However, linked to US low interest rates, Chinese sterilization policies and potentially subsidized capital allocation in China the real yuan/dollar rate is undervalued. This has caused -both in China and the United States- structural distortions and threatens to undermine global growth and stability. We propose Sino-American policy coordination to escape from the policy dilemma, which continues to drive global imbalances.
Keywords: F15; F31; F33; 330; China; exchange rate; financial stability; economic stability; international policy coordination; currency war; Wechselkurspolitik; US-Dollar; Zahlungsbilanzungleichgewicht; Internationale Währungspolitik; China; USA